The role of red-cell distribution width (RDW) and mean platelet volume (MPV) as biomarkers of community-acquired pneumonia (CAP) severity - Edy Purwanto; Reza Ishak Estiko; Firdausia Rahma Putri; Linda Rosita; Rahma Yuantari (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2023)
Community-acquired pneumonia (CAP) remains a leading cause of morbidity and mortality worldwide. Red-cell distribution width (RDW) and mean platelet volume (MPV) are two parameters included in complete blood count (CBC). It is simple, inexpensive, and widely available in any hospital. Many previous studies have shown that RDW and MPV can be used as supporting biomarkers for CAP, but the study in this area remains limited. This study aims to investigate the relationship between RDW and MPV with the severity of CAP and their potential as biomarkers. We conducted a scoping review of original articles using PubMed, Springer Link, Taylor and Francis, EBSCO, Cochrane Library, Google Scholar, Medline, Science Direct, Wiley, and Portal Garuda. Only articles published between 2012 and 2022 in English or Indonesian were included. Out of 11,852 articles reviewed, only 18 met the criteria for the focus on using RDW, MPV, or both as biomarkers for CAP. The details of these studies, including their research design, internal and external validity, and key results, are presented. The results show that increased RDW and MPV levels correlate with higher morbidity and mortality rates among CAP patients. Elevated levels of RDW (>14%) and MPV (>8.1 fL) can predict and acts as a biomarker of CAP severity. Thus, measuring RDW and MPV may give physicians a way to anticipate the outcomes for patients with CAP, helping them make and implement decisions, either alone or in combination with other established methods.